An evaluation of corporate governance legal frameworks in Nigeria: lessons from international organisations and other jurisdictions - Iguodala, Egbe (Department of Commercial Law, 2016)
There is a global trend in the international community, within countries, and within corporate organizations for the promotion of good corporate governance practices. The aim is to foster sustainable development in countries and particularly within corporations at local, national, regional and international levels. This is because emerging reports and research seem to suggest that the effective implementation and practice of good corporate governance principles in a country promotes sustainable development and foreign direct investment, thus boosting the economy of that country. By implication it is only corporations which adopt good corporate governance practices that will achieve sustainable growth and development domestically and internationally in the competitive business environment. In Nigeria, given the fact that the practice of good governance by most corporate organizations is still a challenge, there is therefore a need for a corporate governance regulation that will serve as a baseline standard applicable to all companies registered, whether public or private. Accordingly, this thesis will be examining the existing corporate governance regulations and the newly released draft national corporate governance code in Nigeria to ascertain whether or not they address current corporate governance challenges and their compliance with international best practices.